2021
DOI: 10.30574/gscbps.2021.17.3.0346
|View full text |Cite
|
Sign up to set email alerts
|

Randomized allocation of oocytes to IVF or ICSI for IVF-naïve cases with unexplained infertility in an IVF-ICSI Split protocol favors ICSI to optimize live birth outcomes

Abstract: In assisted reproduction treatments (ART), applying the ICSI method for fertilization of oocytes rather than traditional IVF method, is regarded as controversial for two reasons, namely utility and safety. Our study examines an IVF-ICSI Split model for couples with unexplained infertility, where male factor is meticulously excluded and ART is conducted by a strict algorithm, a commitment to blastocyst culture, along with single embryo transfers and a high commitment to cryopreservation. From 242 treatment cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…The cumulative live birth rate (CLBR) represents the live births arising from ET and FET procedures, from a single oocyte pick-up (OPU). Following our SDF studies with the Halosperm test reported firstly in 2016 [27] and a second study in 2021 [31], we have encouraged all new cases presenting to PIVET, especially those who have never had ART procedures elsewhere, i.e., IVF-naïve cases, to undergo an IVF-ICSI Split modality ensuring that all non-male factor cases have the best opportunity to achieve fertilisation and generate some embryos (avoiding the 5% chance of complete failed fertilisation and 15% chance of reduced fertilisation). A study which analysed four controlled and prospective trials, also found that those authors were unanimous in their conclusion that total fertilization failure of an IVF cycle can be prevented and fertilization can be improved if half of sibling oocytes are subjected to ICSI [32].…”
Section: Live Birthmentioning
confidence: 96%
See 1 more Smart Citation
“…The cumulative live birth rate (CLBR) represents the live births arising from ET and FET procedures, from a single oocyte pick-up (OPU). Following our SDF studies with the Halosperm test reported firstly in 2016 [27] and a second study in 2021 [31], we have encouraged all new cases presenting to PIVET, especially those who have never had ART procedures elsewhere, i.e., IVF-naïve cases, to undergo an IVF-ICSI Split modality ensuring that all non-male factor cases have the best opportunity to achieve fertilisation and generate some embryos (avoiding the 5% chance of complete failed fertilisation and 15% chance of reduced fertilisation). A study which analysed four controlled and prospective trials, also found that those authors were unanimous in their conclusion that total fertilization failure of an IVF cycle can be prevented and fertilization can be improved if half of sibling oocytes are subjected to ICSI [32].…”
Section: Live Birthmentioning
confidence: 96%
“…Certain female factors are also encouraged to undertake ICSI, particularly where few oocytes are recovered (<4), or those with poorly explained infertility where intra-uterine insemination (IUI) treatments have failed and where either of the gametes (oocytes or spermatozoa) have been cryopreserved. Finally, those cases who have previously under-taken an IVF-ICSI Split modality for unexplained infertility will need little persuasion to undertake ICSI treatments, as over 25% of patients with unexplained infertility may have disordered zona pellucida-induced acrosomal reaction (DZPIAR) [36] and subsequently the ICSI fertilization rates were better than IVF-Only [31].…”
Section: Icsi-only (Icsi) Modality (809% Of Cycles)mentioning
confidence: 99%